Adivinanzas audiovisuales para ejercitar el pensamiento creativo infantil - Montalvo Castro, Jorge Andrés (2011)
Solving riddles involves association of ideas, analysis of metaphors, and discovery of analogies. Therefore, promoting this type of children’s entertainment is a way to develop creative thinking. However, there is a problem: traditional riddles are literary forms that correspond to a pre-digital era. How can we increase its acceptance among the digital natives? One way might be creating audiovisual riddles specially designed for YouTube. In this research we made five prototypes of audiovisual riddles with different creative characteristics and validated them among 8-12 years old students. The validation results helped us to identify the attitudes, reactions, interpretations and ways of thinking of children when they try to solve such riddles. We also identified the resources of language and creative formats that fit best in audio-visual riddles. The outcome of this research emphasizes the need to correctly formulate the audiovisual riddle statements and their «clues» for children; this way we assure an intellectual and emotional satisfaction when solving them. It also concludes that reading or listening to traditional riddles are cognitive and sensory experiences that are very different from interacting with the same riddle in a multimedia language. Finally, we discuss and analyze the mediating role of the teacher and the importance of collaborative learning in educational projects using digital technologies.